Evaluation of Viability and Proliferation Profiles on Macrophages Treated with Silica Nanoparticles In Vitro via Plate-Based, Flow Cytometry, and Coulter Counter Assays. (14th November 2012) - Bancos, S.; Tsai, D.-H.; Hackley, V.; Weaver, J. L.; Tyner, K. M.
Abstract : Nanoparticles (NPs) are known to interfere with many high-throughput cell viability and cell proliferation assays, which complicates the assessment of their potential toxic effects. The aim of this study was to compare viability and proliferation results for colloidal silica (SiO2 NP; 7 nm) in the RAW 264.7 mouse macrophage cell line using three different techniques: plate-based assays, flow cytometry analysis, and Coulter counter assays. Our data indicate that CellTiter-Blue, XTT, and CyQuant plate-based assays show increased values over control at low SiO2 NPs concentrations (0.001–0.01 g/L). SiO2 NPs show little-to-no interference with flow cytometry and Coulter counter assays, which not only were more reliable in determining cell viability and proliferation at low concentrations in vitro, but also identified changes in cell granularity and size that were not captured by the plate-based assays. At high SiO2 NP concentrations (1 g/L) all techniques indicated cytotoxicity. In conclusion, flow cytometry and Coulter counter identified new cellular features, and flow cytometry offered more flexibility in analyzing the viability and proliferation profile of SiO2 NP-treated RAW 264.7 cells.